2022
DOI: 10.1093/eurjcn/zvac016
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between mutuality and contributions to self-care in family caregivers of patients with heart failure: multiple mediating effects of resilience and self-efficacy

Abstract: Aims Previous studies have indicated a positive association between mutuality and caregiver contributions to heart failure self-care (CC-HFSC). However, little is known about the underlying mechanisms in the relationship. This study aimed to determine whether resilience and self-efficacy play multiple mediating roles in the association between mutuality and CC-HFSC. Methods and results In this cross-sectional, correlational s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…In the meanwhile, we found that caregivers' mutuality partially mediated the actor effect of their own benefit finding on contributions to self-care management. Previous studies have indicated that benefit finding was positively related to mutuality in caregivers of patients with HF, 34 and caregivers' mutuality was positively associated with their contributions to HF self-care management 29 . Our results confirmed the positive association between benefit finding and mutuality, the positive association between mutuality and self-care management, and the mediation effect of mutuality between benefit finding and self-care management in patients with HF as well as in their family caregivers.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In the meanwhile, we found that caregivers' mutuality partially mediated the actor effect of their own benefit finding on contributions to self-care management. Previous studies have indicated that benefit finding was positively related to mutuality in caregivers of patients with HF, 34 and caregivers' mutuality was positively associated with their contributions to HF self-care management 29 . Our results confirmed the positive association between benefit finding and mutuality, the positive association between mutuality and self-care management, and the mediation effect of mutuality between benefit finding and self-care management in patients with HF as well as in their family caregivers.…”
Section: Discussionsupporting
confidence: 87%
“…61 When facing illness, patients' positive responses could cause caregivers to experience more emotional support and higher self-gain from caregiving, thus improving their perceived mutuality with patients and inspiring them to overcome obstacles in HF management. 23,29,62 In summary, our findings emphasized the significance of mutuality and the interplay between HF patient-caregiver dyads, providing new paths for enhancing dyadic benefit finding and mutuality to improve patients' self-care management and caregivers' contributions to self-care management. This study brought some implications for research and practice.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…According to Bandura’s theory, self-efficacy refers to an individual’s belief in one’s ability to engage in healthy activities ( 18 ). Self-efficacy is a protective factor of resilience and is significantly correlated with medical coping modes ( 19 , 20 ). Adopting positive coping styles can improve patients’ self-efficacy, making them more confident in their ability to face the disease and seek help from others.…”
Section: Introductionmentioning
confidence: 99%